2022
DOI: 10.1177/10963480221116047
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Tourism Experiences and Mental Restoration

Abstract: Virtual reality is providing new opportunities for health and well-being, organizational learning, and tourism management. The study reported in this paper aims to examine whether engaging in a virtual reality tourism experience could function as a restorative intervention strategy to enhance mental well-being of employees in the workplace. The study employed a lab-based pre–post experimental design to test the effectiveness of a virtual reality tourism experience, involving a nature-based marine setting, to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…VTE is the total of the tourists’ cognitive and emotional responses regarding their interaction with the virtual environment (Godovykh et al, 2022). Previous research has shown that enjoyable VTEs positively affect the visit intentions of tourists (Alyahya & McLean, 2022; Atzeni et al, 2022; Choi et al, 2018; Godovykh et al, 2022; Kim et al, 2020; Lee & Kim, 2021; Lu et al, 2022; McLean & Barhorst, 2022; Tussyadiah et al, 2018; Ying et al, 2022; Yuce et al, 2020) and can promote destinations (Walters et al, 2022; Zirbes, 2021). For example, in Lu and colleagues’ (2022) study, participants who had seen a museum for the first time online stated that they would like to visit the museum in the future.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…VTE is the total of the tourists’ cognitive and emotional responses regarding their interaction with the virtual environment (Godovykh et al, 2022). Previous research has shown that enjoyable VTEs positively affect the visit intentions of tourists (Alyahya & McLean, 2022; Atzeni et al, 2022; Choi et al, 2018; Godovykh et al, 2022; Kim et al, 2020; Lee & Kim, 2021; Lu et al, 2022; McLean & Barhorst, 2022; Tussyadiah et al, 2018; Ying et al, 2022; Yuce et al, 2020) and can promote destinations (Walters et al, 2022; Zirbes, 2021). For example, in Lu and colleagues’ (2022) study, participants who had seen a museum for the first time online stated that they would like to visit the museum in the future.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Entertaining and informative online environments can make a museum more exciting and familiar to prospective tourists (Choi et al, 2016), which can lead to an interaction effect on attitudes and subjective norms. Since VTEs require significant mental effort and intense cognitive processing (Walters et al, 2022), an increase in the level of enjoyment from the VTE can lead to more vivid and pleasant memories and increase the influence of attitudes and subjective norms on visit intentions. Furthermore, VTEs provide hedonic value and influence tourists’ liking and interest in the actual environment (Tussyadiah et al, 2018; Yuce et al, 2020), so the enjoyment from a VTE can strengthen the influence of attitudes and subjective norms on visit intentions.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of virtual marine environments on psychological recovery and mental fatigue were tested using a comparative experiment. The results showed that the 3-minute virtual tourism experience can improve the attention of employees and promote their mental health (Walters et al 2022). Using a mixed research approach, Fiocco et al (2021) studied the psychological recovery of elderly people in nursing homes after VR tours.…”
Section: Recovery Effects Of Virtual Tourismmentioning
confidence: 99%
“…The use of smart tourism technologies enriches tourism experiences and satisfaction by facilitating novelty seeking, especially in the pre-trip planning stage (Goo et al, 2022). Digital reality technologies can help “people to imagine their presence at ‘possible new worlds’ that free them from here and now” and deliver social experiential value (Hoyer et al, 2020, p. 63) and, more importantly, provide an opportunity to promote real experiences at destinations (Walters et al, 2022). Bogicevic and colleagues (2019) argued that a heightened sense of presence could explain how VR stimuli motivate tourism brand experience, suggesting that a positive sense of presence could spill over to tourism brand experiences.…”
Section: Theoretical Backgrounds and Hypotheses Developmentmentioning
confidence: 99%